Development of the scale for attitude toward new foods - Ozgen, Leyla; Benli, Mehlika; Turkmen, Fatih (Progress in Nutrition, 2019)
Aim: This study aimed to develop an instrument to assess consumer attitude toward new foods. Methods: This was a descriptive study. The five-point Likert-type scale comprised three subscales and 25 items. In the study, the “Demographic Information Form,” the “Scale for Attitude toward New Foods” (SATNF) and the “Innovativeness Scale” (IS) were used as data collection instruments. Study group: The study sample comprised 300 respondents selected with convenience sampling. The results of the factor analysis performed to test construct validity yielded item factor loadings varying between 0.32 and 0.70 while Cronbach’s alpha values for the skepticism, innovativeness and traditionalism subscales were computed as 0.74, 0.80 and 0.72, respectively. The applicability of factor analysis to the data structure was tested with a Kaiser-Meyer-Olkin test (0.76) and a Bartlett’s test of sphericity (X2 = 1855.123; p